Modified singular spectrum analysis in identifying temporal torrential rainfall patterns over Peninsular Malaysia - Shazlyn Milleana Shaharudin (Tanjong Malim, 2018)
Modified singular spectrum analysis in identifying temporal torrential rainfall patterns over Peninsular Malaysia by Shazlyn Milleana Shaharudin